The evaluation of Business Intelligence maturity level in Iranian banking industry - Najmi, M; Sepehri, M; Hashemi, S (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
Business intelligence (BI) is a managerial concept helping managers and organizations to manage information and make factual decisions. Some have introduced Business Intelligence as a process of turning data into information and then into knowledge. This concept has become a popular trend for businesses interested in adding value to their decision making processes. Measurement of maturity in implementing Business Intelligence process in organizations is considered a critical issue. Business intelligence like software development is a process, which expressed in terms of components such as artifacts and workflows. Capability Maturity Model Integrated (CMMI) is developed to define different levels of software process maturity. The concepts underlying CMMI have been defined different maturity levels for a business intelligence process. The current methods for measurement of Business Intelligence maturity are reviewed introducing the application of CMMI as a new measurement tool for this purpose. The main contribution of this research is to apply CMMI model in BI field, specifically in banking industry in Iran. Also this paper makes a contribution on the empirical knowledge on the topic. It determines in which level of maturity Iranian banks stand in case of implementing Business Intelligence process.